Biopharmaceutical Informatics: supporting biologic drug development via molecular modelling and informatics. (3rd February 2017) - Kumar, Sandeep; Plotnikov, Nikolay V.; Rouse, Jason C.; Singh, Satish K.
Abstract: Objectives: The purpose of this article is to introduce an emerging field called 'Biopharmaceutical Informatics'. It describes how tools from Information technology and Molecular Biophysics can be adapted, developed and gainfully employed in discovery and development of biologic drugs. Key Findings: The findings described here are based on literature surveys and the authors' collective experiences in the field of biologic drug product development. A strategic framework to forecast early the hurdles faced during drug product development is weaved together and elucidated using chemical degradation as an example. Efficiency of translating biologic drug discoveries into drug products can be significantly improved by combining learnings from experimental biophysical and analytical data on the drug candidates with molecular properties computed from their sequences and structures via molecular modeling and simulations. Summary: Biopharmaceutical Informatics seeks to promote applications of computational tools towards discovery and development of biologic drugs. When fully implemented, industry‐wide, it will enable rapid materials‐free developability assessments of biologic drug candidates at early stages as well as streamline drug product development activities such as commercial scale production, purification, formulation, analytical characterization, safety and in vivo performance.